121k views
3 votes
Look at image shown simplify expression and write answer without negative exponents please

Look at image shown simplify expression and write answer without negative exponents-example-1

1 Answer

4 votes

Answer:

The expression without a negative exponent will be:


(8x^(-4)y^(-8))/(-2xy^5)=-(4)/(x^5y^(13))

Explanation:

Given the function


(8x^(-4)\:y^(-8))/(-2xy^5)


\mathrm{Apply\:the\:fraction\:rule}:\quad (a)/(-b)=-(a)/(b)


(8x^(-4)\:y^(-8))/(-2xy^5)=-(8x^(-4)y^(-8))/(2xy^5)\\


\mathrm{Divide\:the\:numbers:}\:(8)/(2)=4


=-(4x^(-4)y^(-8))/(xy^5)


\mathrm{Apply\:exponent\:rule}:\quad (x^a)/(x^b)=(1)/(x^(b-a))


=-(4y^(-8))/(x^5y^5)


\mathrm{Apply\:exponent\:rule}:\quad (x^a)/(x^b)=(1)/(x^(b-a))

i.e.
(y^(-8))/(y^5)=(1)/(y^(5-\left(-8\right)))

so the expression becomes


(8x^(-4)\:y^(-8))/(-2xy^5)=-(4)/(x^5y^(5-\left(-8\right)))


=-(4)/(x^5y^(13))

Therefore, the expression without a negative exponent will be:


(8x^(-4)y^(-8))/(-2xy^5)=-(4)/(x^5y^(13))

User Sheinis
by
6.0k points